Survey on cryptocurrency security attacks and detection mechanisms - Almamoori, Amenah Abdulabbas; Bhaya, Wesam S. (Institute of Advanced Engineering and Science, 2023)
Cryptocurrencies have become extremely popular as a form of payment in recent years. They are supported by blockchain, a cutting-edge advanced technology that makes extensive use of cryptographic mechanisms and other sophisticated distributed computing techniques. On these grounds, cryptocurrencies have been a target of several attacks. Cyber-attacks, for example, are exogenous events that can robustly affect cryptocurrencies by influencing their stabilization of price and market valuation. This study describes an overview of cybercriminals’ activities on cryptocurrencies. It provides a detailed discussion on the most popular types of attacks on the cryptocurrency ecosystem. Moreover, it provides possible countermeasures to these attacks. Finally, it produces insights into the most impactful attacks on cryptocurrencies and the best methods that have been proposed for detecting cryptocurrency attacks. The main goal of this survey is to obtain a thorough understanding of cryptocurrency attacks, which have been the subject of major studies concerning financial risks on cryptocurrency. A large number of existing publications have reviewed and assessed various forms of attacks to achieve this goal. However, these works have considerably flawed. To the best of our knowledge, the present survey sheds light on future research directions.